Indian Diplomacy: the Study of India and Neighboring Country: - (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Despiteall its diverse regional contradictions it is often acknowledged that Indiaholds together a unique Indian integrity. The paper looks at the evolution ofIndian diplomacy n close connection with ancient history and literature of theland. It attempts to bring out the psyche of Indian approach towards theforeign through the years and tries to analyse the reasons that has made thecountry 'adaptive' in the treatment of foreigners and her oreign - rulers. Itsummarises on three-core focal points shaping the growth of India'scross-border dealings after the country's independence and 'democracy'.